Epididymal Polar Dissociation: A Previously Undescribed Anatomical Variant. (4th May 2014) - McCain, Stephen; McCain, Scott; Mark, David; Brown, Robin
Abstract : The normal male external genitalia include the testicles with the epididymis attached posteriorly and the vas deferens arising from this. This case describes an anatomical variation of this normal anatomy not previously reported in the literature. A 17-year-old boy presented with symptoms of intermittent testicular torsion and underwent scrotal exploration. On the left side there was a bell-clapper deformity with the epididymis separated into two parts with the lower pole high in the scrotum and attached to the tunica vaginalis. A normal vas deferens was seen to arise from the isolated lower pole of the epididymis. There was no connection between the vas deferens and the testis or upper pole of epidiymis. This case reminds us of the possibility of anatomical variations and the importance of keeping them in mind to prevent complications at time of surgery.